A microstructured fiber and a method for preparing the same

Through wet spinning process and physical foaming method, microstructured fibers with controllable pore size and porosity were prepared, which solved the scale and safety problems of microstructured fiber preparation in the prior art, and achieved the improvement of lightweight and thermal insulation performance.

CN114481357BActive Publication Date: 2025-03-11WUHAN XINRUNXING MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111644282.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-03-11
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

Existing spinning devices cannot achieve continuous large-scale preparation of microstructured fibers, and there are problems such as foaming agents being prone to leakage and chemical reactions to produce harmful gases, which limits their application.

Method used

Microstructured fibers are prepared by wet spinning process, and fibers with controlled pore size and porosity are prepared by wrapping thermally expanded microspheres and thermoplastic polymers in the fibers.

Benefits of technology

Microstructured fibers that achieve lightweight and good thermal insulation properties, and the pore structure of the fibers can be adjusted as needed, suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003443182970000161
    Figure BDA0003443182970000161
  • Figure BDA0003443182970000261
    Figure BDA0003443182970000261
  • Figure BDA0003443182970000271
    Figure BDA0003443182970000271
Patent Text Reader

Abstract

The present application discloses a microstructure fiber, comprising a core layer and a cladding, wherein the cladding covers the core layer, the core layer has a microstructure, the core layer comprises a first polymer and heat-expandable microspheres, and the cladding comprises a second thermoplastic polymer; or the core layer and the cladding both have a microstructure, the core layer comprises a third polymer, the third polymer comprises a water-soluble polymer and / or a water-dispersible polymer, and the cladding comprises a fourth thermoplastic polymer. The microstructure fiber has good thermal insulation properties, and its pore size, porosity and pore morphology can be effectively controlled by adjusting process parameters, and a corresponding preparation process is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fiber manufacturing, and in particular to a microstructure fiber and a manufacturing method thereof. Background Art

[0002] The spinning device is a machine that forms a fiber-forming polymer solution or melt into a filament. According to different fiber spinning methods, traditional spinning is divided into wet spinning, dry spinning and melt spinning. Wet spinning is a process in which a thin stream of spinning stock solution is squeezed out from the spinneret and enters a coagulation bath. The solvent in the thin stream of stock solution diffuses into the coagulation bath, and the coagulant penetrates into the thin stream, so that the fiber-forming polymer in the thin stream of stock solution reaches a critical concentration and precipitates in the coagulation bath to form fibers. Melt spinning is a spinning method in which a polymer is heated and melted, extruded through a spinneret, and cooled and solidified in the air to form fibers. Melt spinning does not require solvents and precipitants, and the equipment is simple and the process flow is short. However, the equipment requires a high voltage and a high operating temperature.

[0003] There are many defects in the preparation of microstructured fibers at present. For example, the foaming agent of the patent with application number CN201510378201.X is easy to leak and cannot be washed with water. In the patent application with application number CN201710859980.4, a large amount of harmful gases are produced during chemical reactions, and it cannot be prepared in large quantities, which limits its specific application.

[0004] Currently available spinning devices are unable to achieve continuous and large-scale preparation of microstructured fibers, and this shortcoming severely limits their application in various scenarios.

[0005] The shortcomings of the fibers or impregnated foaming materials can be effectively avoided by this patent, and a physical foaming method is adopted, which is green and environmentally friendly. At the same time, a coaxial structure is used to wrap the foaming agent in the fiber, which is not easy to leak and can be washed. Due to its controllable fiber closed-cell size, it can achieve lightweight and good thermal insulation performance. In addition, the fibers are woven into fabrics, which have wearable properties such as flexibility and breathability, are easy to prepare, and are suitable for large-scale industrial production. Summary of the invention

[0006] In order to solve the technical problems existing in the prior art, the present invention provides a microstructure fiber prepared based on a wet spinning process. The pore size and shape of the prepared microstructure fiber are controllable, so that the fiber has light weight and good thermal insulation performance.

[0007] The technical solution of the present invention is as follows:

[0008] 1. A microstructure fiber, comprising a core layer and a cladding layer, wherein the cladding layer covers the core layer, the core layer has a microstructure, the core layer comprises a first polymer and heat-expandable microspheres, and the cladding layer comprises a second thermoplastic polymer;

[0009] Further preferably, the diameter ratio of the core layer and the cladding layer in the cross section of the microstructure fiber is 1:1.1-1:5.

[0010] 2. The microstructure fiber according to item 1, wherein the pore size of the microstructure of the core layer is 0.1 to 200 μm, the porosity of the microstructure of the core layer is 5 to 99%, and the specific surface area of ​​the microstructure fiber is 1 to 400 m 2 / g;

[0011] Preferably, the pore size is 10-40 μm, the porosity is 70-90%, and the specific surface area is 50-100 m 2 / g.

[0012] 3. The microstructured fiber according to item 1, wherein the first polymer comprises a first thermoplastic polymer or a first thermosetting polymer, and the first thermoplastic polymer is selected from one or more of polyacrylonitrile, polyacrylic acid, polymethacrylic acid, polyacrylaldehyde, polyacrylamide, polypropylene imine, polyhydroxyacrylate, polyacrylate butylene nitrile, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl acetal, polyurethane, polyimide, polybutylene terephthalate, polyethylene terephthalate, polyarylate, polyvinyl acetate, and polycaprolactone, preferably polyurethane;

[0013] The first thermosetting polymer is selected from one or more of polydimethylsiloxane, epoxy resin, and phenolic resin, preferably polydimethylsiloxane.

[0014] 4. In the microstructured fiber as described in item 1, the second thermoplastic polymer is selected from one or more of polyurethane, polylactic acid, polycaprolactone, polyamide, polyanhydride, polyimide, polyacrylonitrile, polyacrylic acid, polymethacrylic acid, polyacrylaldehyde, polyacrylamide, polypropylene imine, polyhydroxyacrylate, polyacrylate butylene nitrile, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl acetal; preferably polyacrylonitrile.

[0015] 5. A microstructure fiber, comprising a core layer and a cladding layer, wherein the cladding layer covers the core layer, the core layer and the cladding layer both have a microstructure, the core layer comprises a third polymer, the third polymer comprises a water-soluble polymer and / or a water-dispersible polymer, and the cladding layer comprises a fourth thermoplastic polymer;

[0016] Preferably, the third polymer is a water-soluble polymer. Further preferably, the diameter ratio of the core layer and the cladding layer of the cross section of the microstructure fiber is 1:1.1-1:5.

[0017] 6. The microstructure fiber as described in item 5, wherein the pore size of the microstructure of the core layer is 0.1 to 200 μm, the pore size of the microstructure of the cladding layer is 0.1 to 100 μm, the porosity of the microstructure of the core layer is 5 to 99%, the porosity of the microstructure of the cladding layer is 5 to 99%, and the specific surface area of ​​the microstructure fiber is 1 to 400 m 2 / g;

[0018] Preferably, the pore size of the microstructure of the core layer is 0.2-100 μm, the pore size of the microstructure of the cladding layer is 0.2-100 μm, the porosity of the microstructure of the core layer is 70-90%, the porosity of the microstructure of the cladding layer is 70-90%, and the specific surface area is 50-100 m 2 / g.

[0019] 7. The microstructure fiber according to item 5, wherein the water-dispersible polymer is selected from one or more of polyacrylonitrile, polyvinylidene fluoride, phenylenediamine, polyvinyl acetal, and polyvinyl chloride;

[0020] The water-soluble polymer is selected from one or more of sodium carboxymethyl cellulose, regenerated cellulose, silk protein, chitosan and polyvinyl alcohol.

[0021] 8. The microstructured fiber as described in item 5, wherein the fourth thermoplastic polymer is selected from one or more of polyurethane, polyvinyl alcohol, polylactic acid, polycaprolactone, polyamide, polyanhydride, and polyimide; preferably polyurethane.

[0022] 9. A process for preparing microstructured fibers, comprising the following steps:

[0023] i. configuring a spinning solution, wherein the spinning solution comprises a core layer material and a cladding solution;

[0024] ii. Spinning process: wet spinning the spinning solution to obtain primary fibers;

[0025] iii. Post-treatment process: post-treating the primary fibers to obtain microstructured fibers;

[0026] Preferably, the post-treatment process includes a heat treatment process or a cold treatment process.

[0027] 10. The preparation process according to item 9, wherein the post-treatment process is a heat treatment process, and the temperature of the heat treatment of the spun fiber is 30°C to 300°C, preferably 85°C to 160°C;

[0028] Further preferably, the heat treatment is electric heating treatment.

[0029] 11. The preparation process according to item 10, wherein the core layer raw material comprises a first polymer and heat-expandable microspheres;

[0030] The first polymer includes a first thermoplastic polymer or a first thermosetting polymer, and the first thermoplastic polymer is selected from one or more of polyacrylonitrile, polyacrylic acid, polymethacrylic acid, polyacrylaldehyde, polyacrylamide, polypropylene imine, polyhydroxyacrylate, polyacrylate crotonitrile, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl acetal, polyurethane, polyimide, polybutylene terephthalate, polyethylene terephthalate, polyarylate, polyvinyl acetate, and polycaprolactone, preferably polyurethane;

[0031] The first thermosetting polymer is selected from one or more of polydimethylsiloxane, epoxy resin and phenolic resin.

[0032] 12. The preparation process according to item 11, wherein the coating solution comprises a second thermoplastic polymer;

[0033] The second thermoplastic polymer is selected from one or more of polyurethane, polylactic acid, polycaprolactone, polyamide, polyanhydride, polyimide, polyacrylonitrile, polyacrylic acid, polymethacrylic acid, polyacrylaldehyde, polyacrylamide, polypropylene imine, polyhydroxyacrylate, polyacrylate butylene nitrile, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl acetal.

[0034] 13. In the preparation process as described in any one of items 10 to 12, in step i, the solvent used to form the spinning solution is selected from one or more of chloroform, dichloromethane, N,N-dimethylformamide, tetrahydrofuran solvent, chloroform, acetone, tetrachloroethylene, methyl acetate, ethyl acetate, ethylenediamine, ethyl acetate, and toluene.

[0035] 14. The preparation process according to item 9, wherein the post-treatment process is a cold treatment process, the cold treatment process includes a cooling treatment and a freeze-drying treatment, and the temperature of the cooling treatment of the spun fiber is -300°C to -10°C, preferably -196°C to -100°C;

[0036] Preferably, in the cooling process, a refrigerant is used to cool the spun fibers;

[0037] Further preferably, the refrigerant is selected from one or more of liquid nitrogen, dry ice, ethanol and ethylene glycol.

[0038] 15. The preparation process according to item 14, wherein the core layer raw material comprises a third polymer, and the third polymer comprises a water-soluble polymer and / or a water-dispersible polymer;

[0039] The water-dispersible polymer is selected from one or more of polyacrylonitrile, polyvinylidene fluoride, phenylenediamine, polyvinyl acetal, and polyvinyl chloride;

[0040] The water-soluble polymer is selected from one or more of sodium carboxymethyl cellulose, regenerated cellulose, silk protein, chitosan and polyvinyl alcohol.

[0041] 16. The preparation process according to item 15, wherein the coating solution comprises a fourth thermoplastic polymer;

[0042] The fourth thermoplastic polymer is selected from one or more of polyurethane, polyvinyl alcohol, polylactic acid, polycaprolactone, polyamide, polyanhydride, and polyimide.

[0043] 17. In the preparation process as described in item 15 or 16, in step i, the solvent of the coating solution is selected from one or more of N,N-dimethylacetamide, N,N-dimethylformamide, methanol, formic acid, chloroform, acetone, tetrachloroethylene, methyl acetate, ethyl acetate, ethyl acetate, and toluene.

[0044] 18. The preparation process according to any one of items 9 to 17, wherein in step ii, the spinning process comprises an extrusion process and a molding process;

[0045] In the extrusion process, a core layer raw material is placed in a core layer extruder, a cladding solution is placed in a cladding extruder, and then wet spinning is performed;

[0046] Preferably, the extrusion velocity of the core layer raw material is 0.01 to 100 m / min, preferably 1 to 5 m / min; the extrusion velocity of the cladding solution is 0.01 to 100 m / min, preferably 1 to 5 m / min.

[0047] 19. In the preparation process as described in item 18, in the extrusion process, the spinning solutions are extruded in parallel.

[0048] 20. The preparation process according to item 19, wherein in the molding process, the spinning solution is molded using a fiber molding solution;

[0049] Preferably, the fiber forming liquid is selected from one or more of ethanol, methanol, water, ethylene glycol, isobutyl alcohol, isopentanol, benzyl alcohol, sodium sulfate, and sodium hydroxide solution, preferably water.

[0050] Technical effects of the present invention:

[0051] (1) The pore structure of the microstructured fiber provided by the present invention can be effectively adjusted as needed, such as effectively controlling its pore size, porosity and pore morphology. The obtained microstructured fiber has light weight and good thermal insulation performance.

[0052] (2) When the microstructure fiber provided by the present invention is prepared by a heat treatment process, heat-expandable microspheres are used, and the coating is solidified by wet spinning solvent exchange. During this process, the heat-expandable microspheres do not change. During the heat treatment, the heat-expandable microspheres expand, that is, the expansion process is after the fiber is formed, and the fiber closed-cell size is controllable, and the heat-expandable microspheres are wrapped inside, which is not easy to leak.

[0053] (3) When the microstructure fiber provided by the present invention is prepared by a cold treatment process, the spinning solution is extruded through an extruder controlled by an extrusion pump, and after being formed by a fiber forming solution, when it is subjected to a low temperature treatment, the water in the fiber condenses into ice crystals. At the same time, the polymer is displaced by the ice crystals and compressed in the gaps between the ice crystals, and then the ice crystals are removed by freeze drying to obtain the microstructure fiber.

[0054] (4) The preparation process of the present invention is simple, and microstructure fibers can be prepared continuously and on a large scale, which is suitable for industrial scale-up applications. Different materials can be designed according to actual needs, and the fiber extrusion unit nozzle structure can be adjusted according to actual needs. Microstructure fibers of different shapes and structures can be prepared, and the fiber structure has excellent fiber structure regulation performance. In addition, the fibers are woven into fabrics, which have wearable properties such as flexibility and breathability, are easy to prepare, and are suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 The diagram of a simplified device of a single-component nozzle for wet spinning in a heat treatment process is shown as a post-treatment process;

[0056] Figure 2 The diagram of a simplified device of a wet spinning multi-component nozzle in a heat treatment process is shown as a post-treatment process;

[0057] Figure 3 The diagram of a simple device of a single-component nozzle for wet spinning in a cold treatment process is shown in the post-treatment process;

[0058] Figure 4 The diagram of a simplified device of a wet spinning multi-component nozzle in a cold treatment process is shown in the post-treatment process;

[0059] Figure 5 This is a simplified schematic diagram of the microstructure fiber obtained in Example 38 (cold treatment temperature is -196°C);

[0060] Figure 6 is a simplified schematic diagram of the microstructured fiber obtained in Example 31 (cold treatment temperature is -100°C);

[0061] Figure 7 is a simplified schematic diagram of the microstructured fiber obtained in Example 2;

[0062] Figure 8is a simplified schematic diagram of the microstructured fiber obtained in Example 10;

[0063] Fig. 9A is a simplified schematic diagram of the microstructured fiber obtained in Example 13;

[0064] Fig. 9B This is a simplified schematic diagram of the microstructured fiber obtained in Example 14. DETAILED DESCRIPTION

[0065] The present invention is described in detail below. Although specific embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.

[0066] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.

[0067] The term "polymer" refers to a polymeric molecule having one or more monomeric species and includes homopolymers and copolymers.

[0068] The terms "preferred" and "preferably" refer to embodiments that may provide certain benefits in certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. In addition, the reference to one or more preferred embodiments does not mean that other embodiments are not applicable, and does not mean that other embodiments are excluded from the scope of the invention of the present invention.

[0069] Reference to "a" chemical compound refers to one or more molecules of the chemical compound, and is not limited to a single molecule of the chemical compound. In addition, the one or more molecules may or may not be the same, as long as they fall within the scope of the chemical compound. Thus, for example, "a" polyester is interpreted to include one or more polymer molecules of the polyester, wherein the polymer molecules may or may not be the same (e.g., different molecular weights and / or isomers).

[0070] The terms "at least one" and "one or more" components are used interchangeably and have the same meaning including both single components and multiple components, and may also be indicated by the suffix "(s)" at the end of the element. For example, "at least one polyester", "one or more polyesters" and "polyester(s)" are used interchangeably and have the same meaning.

[0071] The terms "about," "approximately," and "substantially" as used herein refer to measurable values ​​and measurable ranges due to expected variations known to those skilled in the art (eg, limitations and variability of measurements).

[0072] For example, when recited in the claims, the term "providing" does not mean requiring any specific delivery or receipt of the provided item. Instead, the term "providing" is only used to state the item, which is mentioned in the subsequent elements of the claim for the purpose of clarity and easy reading.

[0073] Unless otherwise indicated, temperatures referred to herein are based on atmospheric pressure (ie, one atmosphere).

[0074] As used herein, "soluble" can be used interchangeably with "decomposable" and "dissolvable" and refers to a material that decomposes in a solution or dispersion. Upon decomposition, the water-dispersible material may decompose into small pieces and / or polymer particles in the solution or dispersion. Some or all of the water-dispersible material may also dissolve into the solution or dispersion upon decomposition.

[0075] The term "polyester" as referred to herein relates to a polymer containing ester functional groups in its backbone. As used herein, the term "sulfopolyester" refers to any polyester containing a sulfonated monomer.

[0076] The term "polyamide" as used herein refers to aliphatic and aromatic polyamides. In the case of aliphatic polyamides, such as nylon 6 and nylon 66, the amide bond is formed by the polycondensation reaction of amino and carboxylic acid groups, wherein water is removed. For aromatic polyamides or "aromatic polyamides", such as Kevlar, acid chlorides are used as monomers. As used herein, the term "sulfopolyamide" refers to any polyamide containing a sulfonated monomer.

[0077] The term "polyurethane" as referred to herein refers to polymers most commonly formed by reacting a diisocyanate or polyisocyanate with a polyol. As used herein, the term "sulfopolyurethane" refers to any polyurethane containing a sulfonic group.

[0078] The term "microstructure" used in the present invention refers to a porous structure, and the pore size of the porous structure is in the micrometer order.

[0079] The present invention provides a microstructure fiber, which comprises a core layer and a cladding layer, wherein the cladding layer covers the core layer, the core layer has a microstructure, the core layer comprises a first polymer and heat-expandable microspheres, and the cladding layer comprises a second thermoplastic polymer.

[0080] The cladding may also be described as a skin layer, and the covering includes partial covering and / or full covering.

[0081] The first polymer includes a first thermoplastic polymer or a first thermosetting polymer, and the first thermoplastic polymer is selected from one or more of polyacrylonitrile, polyacrylic acid, polymethacrylic acid, polyacrylaldehyde, polyacrylamide, polypropylene imine, polyhydroxyacrylate, polyacrylate butylene nitrile, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl acetal, polyurethane, polyimide, polybutylene terephthalate, polyethylene terephthalate, polyarylate, polyvinyl acetate, and polycaprolactone, preferably polyurethane; the first thermosetting polymer is selected from one or more of polydimethylsiloxane, epoxy resin, and phenolic resin, preferably polydimethylsiloxane.

[0082] The heat-expandable microsphere is a high molecular polymer microsphere, comprising a shell composed of a polymer and an inner layer composed of a low-boiling-point alkane gas, wherein the polymer is selected from one or more homopolymers or copolymers or a mixture of homopolymers and copolymers of methacrylic acid and its alkyl esters, acrylic acid and its alkyl esters, acrylonitrile, and acrylamide monomers; the low-boiling-point alkane gas is selected from one or more n-butane, isobutane, isooctane, isopentane, petroleum ether, n-pentane, and neopentane;

[0083] Preferably, the polymer constituting the shell is selected from one or more homopolymers or copolymers of acrylonitrile, acrylic acid, methacrylic acid, or a mixture of homopolymers and copolymers, and the low-boiling alkane gas is selected from isooctane, isopentane or isobutane.

[0084] In one embodiment of the present invention, the heat-expandable microspheres are selected from one or more of 980DU120, 920DU40, 909DU80, 461DU20, 461DU40, and 920DU20 (purchased from Nouryon Chemicals (Ningbo) Co., Ltd.).

[0085] The second thermoplastic polymer is selected from one or more of polyurethane, polylactic acid, polycaprolactone, polyamide, polyanhydride, polyimide, polyacrylonitrile, polyacrylic acid, polymethacrylic acid, polyacrylaldehyde, polyacrylamide, polypropylene imine, polyhydroxyacrylate, polyacrylate butylene nitrile, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl acetal; preferably polyacrylonitrile.

[0086] In a specific embodiment of the present invention, the first polymer is polyurethane, and the heat-expandable microspheres are 980DU120, that is, the core layer is composed of polyurethane and 980DU120.

[0087] In a specific embodiment of the present invention, the first polymer is polydimethylsiloxane, and the heat-expandable microspheres are 920DU40, that is, the core layer is composed of polydimethylsiloxane and 920DU40.

[0088] In a specific embodiment of the present invention, the second thermoplastic polymer is polyacrylonitrile, that is, the cladding layer is composed of polyacrylonitrile.

[0089] The microstructure fiber of the present invention is composed of the core layer and the cladding layer.

[0090] In a specific embodiment of the present invention, the core layer of the microstructure fiber is composed of polyurethane and 980DU120, and the cladding layer is composed of polyacrylonitrile.

[0091] In a specific embodiment of the present invention, the core layer of the microstructure fiber is composed of polydimethylsiloxane and 920DU40, and the cladding layer is composed of polyacrylonitrile.

[0092] In the microstructure fiber provided by the present invention, the pore size of the microstructure of the core layer of the microstructure fiber is 0.1-200 μm, the porosity of the microstructure of the core layer is 5-99%, and the specific surface area of ​​the microstructure fiber is 1-400 m 2 / g;

[0093] Preferably, the pore size is 10-40 μm, the porosity is 70-90%, and the specific surface area is 50-100 m 2 / g.

[0094] In the microstructure fiber provided by the present invention, the diameter ratio of the core layer and the cladding layer in the cross section of the microstructure fiber is 1:1.1-1:5.

[0095] The ratio of the core and cladding diameters in a fiber cross section is also called the core-to-cladding ratio.

[0096] The present invention also provides a process for preparing the above-mentioned microstructured fiber, comprising the following steps:

[0097] i. configuring a spinning solution, wherein the spinning solution comprises a core layer material and a cladding solution;

[0098] ii. Spinning process: wet spinning the spinning solution to obtain primary fibers;

[0099] iii. Post-treatment process: post-treating the primary fibers to obtain microstructured fibers;

[0100] Preferably, the post-treatment process includes a heat treatment process or a cold treatment process.

[0101] In one embodiment of the present invention, the post-treatment process is a heat treatment process, and the temperature for heat treating the as-spun fibers is 30°C to 300°C, preferably 85°C to 160°C.

[0102] In one embodiment of the present invention, the post-treatment process is a heat treatment process, the core layer raw material includes a first polymer and heat-expandable microspheres, and the cladding solution includes a second thermoplastic polymer, as follows:

[0103] The first polymer includes a first thermoplastic polymer or a first thermosetting polymer, and the first thermoplastic polymer is selected from one or more of polyacrylonitrile, polyacrylic acid, polymethacrylic acid, polyacrylaldehyde, polyacrylamide, polypropylene imine, polyhydroxyacrylate, polyacrylate crotonitrile, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl acetal, polyurethane, polyimide, polybutylene terephthalate, polyethylene terephthalate, polyarylate, polyvinyl acetate, and polycaprolactone, preferably polyurethane;

[0104] The first thermosetting polymer is selected from one or more of polydimethylsiloxane, epoxy resin, and phenolic resin, preferably polydimethylsiloxane.

[0105] The heat-expandable microsphere is a high molecular polymer microsphere, comprising a shell composed of a polymer and an inner layer composed of a low-boiling-point alkane gas, wherein the polymer is selected from one or more homopolymers or copolymers or a mixture of homopolymers and copolymers of methacrylic acid and its alkyl esters, acrylic acid and its alkyl esters, acrylonitrile, and acrylamide monomers; the low-boiling-point alkane gas is selected from one or more n-butane, isobutane, isooctane, isopentane, petroleum ether, n-pentane, and neopentane;

[0106] Preferably, the polymer constituting the shell is selected from one or more homopolymers or copolymers of acrylonitrile, acrylic acid, methacrylic acid, or a mixture of homopolymers and copolymers, and the low-boiling alkane gas is selected from isooctane, isopentane or isobutane.

[0107] In one embodiment of the present invention, the heat-expandable microspheres are selected from one or more of 980DU120, 920DU40, 909DU80, 461DU20, 461DU40, and 920DU20 (purchased from Nouryon Chemicals (Ningbo) Co., Ltd.).

[0108] The second thermoplastic polymer is selected from one or more of polyurethane, polylactic acid, polycaprolactone, polyamide, polyanhydride, polyimide, polyacrylonitrile, polyacrylic acid, polymethacrylic acid, polyacrylaldehyde, polyacrylamide, polypropylene imine, polyhydroxyacrylate, polyacrylate butylene nitrile, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl acetal; preferably polyacrylonitrile.

[0109] In one embodiment of the present invention, when the first polymer is a first thermoplastic polymer, the solvent used to form the spinning solution is selected from one or more of chloroform, dichloromethane, N,N-dimethylformamide, tetrahydrofuran solvent, chloroform, acetone, tetrachloroethylene, methyl acetate, ethyl acetate, ethylenediamine, ethyl acetate, and toluene.

[0110] In a specific embodiment of the present invention, when the first polymer is the first thermoplastic polymer, specifically polyurethane, and the heat-expandable microspheres are 980DU120, polyurethane and 980DU120 are dissolved in N,N-dimethylformamide solution to form the core layer material.

[0111] In a specific embodiment of the present invention, the mass fraction of the first thermoplastic polymer ranges from 1 to 30% by weight, and the mass fraction of the heat-expandable microspheres ranges from 0.5 to 20% by weight.

[0112] In one embodiment of the present invention, when the first polymer is a first thermosetting polymer, the first thermosetting polymer and heat-expandable microspheres are mixed, an appropriate amount of curing agent is added, and stirred to form a core layer material, wherein the mass fraction of the first thermosetting polymer is in the range of 50-90%, and the rest is heat-expandable microspheres.

[0113] In one embodiment of the present invention, the first thermosetting polymer is polydimethylsiloxane, the heat-expandable microspheres are 461DU20, and the curing agent is 184 silica gel, which constitute the core layer material.

[0114] The second thermoplastic polymer is polyacrylonitrile, and polyacrylonitrile is dissolved in N,N-dimethylformamide, with the mass fraction of the second thermoplastic polymer ranging from 1 to 30% by weight, to form a cladding solution.

[0115] In one embodiment of the present invention, in the extrusion process, the core layer raw material is placed in a core layer extruder, and the cladding solution is placed in the cladding extruder for wet spinning;

[0116] Preferably, the extrusion flow rate of the core layer raw material is 0.01 to 100 m / min, preferably 1 to 5 m / min, and the extrusion flow rate of the cladding solution is 0.01 to 100 m / min, preferably 1 to 5 m / min.

[0117] In a specific embodiment of the present invention, a solution formed by dissolving polyurethane and 980DU120 in N,N-dimethylformamide constitutes the core layer raw material, and a solution formed by dissolving polyacrylonitrile in N,N-dimethylformamide constitutes the cladding solution.

[0118] In a specific embodiment of the present invention, polydimethylsiloxane, 920DU40 and a curing agent are mixed to form a core layer material, and a solution formed by dissolving polyacrylonitrile in N,N-dimethylformamide forms a cladding solution.

[0119] The present invention provides a microstructure fiber, which includes a core layer and a cladding, wherein the cladding covers the core layer, and both the core layer and the cladding have a microstructure. The core layer includes a third polymer, which includes a water-soluble polymer and / or a water-dispersible polymer, and the cladding includes a fourth thermoplastic polymer.

[0120] The cladding may be described as a skin layer, and the covering may include partial covering and / or full covering.

[0121] Water-soluble polymers, also known as water-soluble macromolecular compounds or water-soluble resins, are hydrophilic polymer materials that can dissolve or swell in water to form solutions or dispersions. The hydrophilicity of water-soluble polymers comes from the presence of hydrophilic groups in their molecules, which not only make the polymer hydrophilic, but also give it many valuable properties, such as chelation, dispersibility, flocculation, friction reduction, thickening, etc. Moreover, the molecular weight of water-soluble polymers can be controlled.

[0122] A water-dispersible polymer is one that, upon decomposition, can decompose into small pieces and / or polymer particles in a solution or dispersion.

[0123] In one embodiment of the present invention, the water-soluble polymer is selected from one or more of sodium carboxymethyl cellulose, regenerated cellulose, silk protein, chitosan, and polyvinyl alcohol.

[0124] In one embodiment of the present invention, the water-dispersible polymer is selected from one or more of polyacrylonitrile, polyvinylidene fluoride, phenylenediamine, polyvinyl acetal, and polyvinyl chloride.

[0125] In a preferred embodiment of the present invention, the third polymer is a water-soluble polymer.

[0126] In one embodiment of the present invention, the fourth thermoplastic polymer is selected from one or more of polyurethane, polyvinyl alcohol, polylactic acid, polycaprolactone, polyamide, polyanhydride, and polyimide; preferably polyurethane.

[0127] In a specific embodiment of the present invention, the third polymer is selected from a mixture of chitosan and polyvinyl alcohol, that is, the core layer is composed of chitosan and polyvinyl alcohol.

[0128] In a specific embodiment of the present invention, the fourth thermoplastic polymer is polyurethane, that is, the cladding layer is composed of polyurethane.

[0129] In the microstructure fiber provided by the present invention, the pore size of the microstructure of the core layer is 0.1-200 μm, the pore size of the microstructure of the cladding layer is 0.1-100 μm, the porosity of the microstructure of the core layer is 5-99%, the porosity of the microstructure of the cladding layer is 5-99%, and the specific surface area of ​​the microstructure fiber is 1-400 m 2 / g.

[0130] Preferably, the pore size of the microstructure of the core layer is 0.2-100 μm, the pore size of the microstructure of the cladding layer is 0.2-100 μm, the porosity of the microstructure of the core layer is 70-90%, the porosity of the microstructure of the cladding layer is 70-90%, and the specific surface area is 50-100 m 2 / g.

[0131] In the microstructure fiber provided by the present invention, the core-to-package ratio of the microstructure fiber is 1:1.1-1:5.

[0132] The present invention also provides a process for preparing the above-mentioned microstructured fiber, comprising the following steps:

[0133] i. configuring a spinning solution, wherein the spinning solution comprises a core layer material and a cladding solution;

[0134] ii. Spinning process: wet spinning the spinning solution to obtain primary fibers;

[0135] iii. Post-treatment process: post-treating the primary fibers to obtain microstructured fibers;

[0136] Preferably, the post-treatment process includes a heat treatment process or a cold treatment process.

[0137] In one embodiment of the present invention, the post-treatment process is a cold treatment process, which includes a cooling treatment and a freeze-drying treatment. The temperature of the cooling treatment of the spun fiber is -300°C to -10°C, preferably -196°C to -100°C.

[0138] In one embodiment of the present invention, in the cooling process, a refrigerant is selected to cool the spun fibers.

[0139] In a specific embodiment of the present invention, the refrigerant is selected from one or more of liquid nitrogen, dry ice, ethanol, and ethylene glycol.

[0140] In one embodiment of the present invention, in the cold treatment process, the core layer raw material includes a third polymer, and the third polymer includes a water-soluble polymer and / or a water-dispersible polymer; the water-dispersible polymer is selected from one or more of polyacrylonitrile, polyvinylidene fluoride, phenylenediamine, polyvinyl acetal, and polyvinyl chloride;

[0141] The water-soluble polymer is selected from one or more of sodium carboxymethyl cellulose, regenerated cellulose, silk protein, chitosan and polyvinyl alcohol.

[0142] In one embodiment of the present invention, based on the total weight of the core layer raw materials, the mass fraction of the water-soluble polymer is in the range of 0-10 weight %.

[0143] In one embodiment of the present invention, based on the total weight of the core layer raw materials, the mass fraction of the water-dispersible polymer is in the range of 0-10 weight %.

[0144] In one embodiment of the present invention, in the cold treatment process, the coating solution includes a fourth thermoplastic polymer, and the fourth thermoplastic polymer is selected from one or more of polyurethane, polyvinyl alcohol, polylactic acid, polycaprolactone, polyamide, polyanhydride, and polyimide, wherein the solvent of the coating solution is selected from one or more of N,N-dimethylacetamide, N,N-dimethylformamide, methanol, formic acid, chloroform, acetone, tetrachloroethylene, methyl acetate, ethyl acetate, ethyl acetate, and toluene.

[0145] In one embodiment of the present invention, based on the total weight of the coating solution, the mass fraction of the fourth thermoplastic polymer is in the range of 1-30 weight %.

[0146] In a specific embodiment of the present invention, the third polymer is a water-soluble polymer, preferably a mixture of polyvinyl alcohol and chitosan, wherein polyvinyl alcohol is dissolved in water, chitosan powder is dissolved in acetic acid solution, and polyvinyl alcohol solution and chitosan solution are mixed uniformly in a certain proportion to obtain a core layer material. Polyurethane is dissolved in N, N-dimethylformamide solution to obtain a cladding solution.

[0147] In one embodiment of the present invention, in step ii, the spinning process includes an extrusion process and a molding process, in which the core layer raw material is placed in a core layer extruder, and the cladding solution is placed in a cladding extruder for wet spinning;

[0148] Preferably, the extrusion velocity of the core layer raw material is 0.01 to 100 m / min, preferably 1 to 5 m / min; the extrusion velocity of the cladding solution is 0.01 to 100 m / min, preferably 1 to 5 m / min.

[0149] In one embodiment of the present invention, the extrusion process can be implemented by a fiber extrusion unit, which includes an extruder, a nozzle, and an extrusion pump that provides power to the extruder. The extrusion pump controls the extrusion flow rate of the spinning solution by squeezing the extruder piston. The extrusion pump can be built-in or external to the fiber extrusion unit to control the extrusion flow rate of the spinning solution. The extrusion pump controls the extrusion of the spinning solution by squeezing the piston of the extruder. The flow rate of the extrusion pump squeezing the piston is 0.01 to 100 m / min, preferably 1 to 5 m / min, for example, 2 m / min.

[0150] The extruder volume can be 100-5000ml, and the inner diameter is between 50-250mm. The extrusion unit nozzle material is selected from but not limited to one or more of titanium, tantalum, niobium, iridium, palladium, rhodium, gold, platinum, nickel, stainless steel, ceramic, quartz, sapphire and special glass, preferably one or more of tantalum, niobium, gold, platinum, ceramic, stainless steel, special glass. The cross-sectional shape of the extrusion unit nozzle is circular, triangular, square, polygonal or other special-shaped structures, preferably circular.

[0151] In one embodiment of the present invention, the nozzle can be a single-component, double-component or multi-component nozzle, wherein the single-component nozzle can prepare single-structure fibers, and the double-component and multi-component nozzles can prepare coaxial, parallel and orange segment structures, preferably a coaxial structure. The number of holes in the nozzle is 1 to 1000 holes, and the number of holes in the double-component and multi-component nozzles is 1 to 64 holes.

[0152] In one embodiment of the present invention, the aperture range of the nozzle is 0.01-2 mm, wherein the aperture range of the single-component nozzle is 0.01-2 mm, preferably 0.02-1 mm; the aperture range of the two-component and multi-component nozzles is 0.05-2 mm, preferably 0.1-1 mm.

[0153] In one embodiment of the present invention, the number of holes of the nozzle is 1 to 500, wherein the number of holes of the single-component nozzle is 6 to 500 holes, and the number of holes of the two-component and multi-component nozzles is 1 to 6 holes.

[0154] In one embodiment of the present invention, the spinning solution is subjected to a molding process using a fiber molding liquid, and the molding process can be performed by a fiber molding unit. The fiber molding unit includes a fiber molding bath and a guide wheel, wherein the fiber molding bath has a length of 300 to 1500 mm, a width of 50 to 200 mm, and is filled with a fiber molding liquid; the guide wheel includes a rotating bearing and a rotating wheel, and the material is selected from but not limited to one or more of glass, ceramic, stainless steel, alloy, and plastic;

[0155] The fiber forming liquid is selected from one or more of ethanol, methanol, water, formic acid, acetic acid, glycerol, ethylene glycol, isobutyl alcohol, isopentanol, benzyl alcohol, sodium sulfate, and sodium hydroxide solution, preferably water.

[0156] In one embodiment of the present invention, the material of the molding bath is selected from one or more of glass, ceramic, stainless steel, alloy and plastic, preferably polytetrafluoroethylene. The rotating bearing and rotating wheel of the guide wheel are both made of ceramic.

[0157] In one embodiment of the present invention, in step iii, the post-treatment process is implemented via a freezing unit or a heating treatment unit.

[0158] In one embodiment of the present invention, the freezing unit includes a freezing tank storing a refrigerant and a freezing pipe, wherein the freezing pipe passes through the bottom of the freezing tank and is in direct contact with the refrigerant. The freezing tank material is one or more of thermal insulation materials such as glass fiber, asbestos, rock wool, silicate, ceramic, foam, etc. More preferably, it is a ceramic material with excellent thermal insulation properties.

[0159] The freezing pipe can be made of heat-conducting metal materials such as copper and aluminum. More preferably, the copper pipe is made of red copper, which has a thermal conductivity of 386.4 W / (m·K) and has excellent thermal conductivity.

[0160] The refrigerant is selected from one or a mixed solution of two or more of liquid nitrogen, dry ice, ethanol, ethylene glycol, etc. The temperature in the freezing tube is -300°C to -10°C. More preferably, it is -196°C to -100°C. Preferably, the freezing tank is provided with a refrigeration mechanism for controlling the temperature of the refrigerant.

[0161] In one embodiment of the present invention, the refrigeration mechanism is a low-temperature constant temperature tank, which is connected to the freezing tank through a refrigerant circulation pipe. The refrigerant circulation pipe is connected between the freezing tank and the refrigeration mechanism, and the refrigerant circulates in the refrigeration mechanism, the refrigerant circulation pipe and the freezing tank to form a closed loop to maintain the low temperature environment in the freezing tank.

[0162] In one embodiment of the present invention, the heat treatment unit includes an electric heating device and a heating tube, the temperature in the heating tube is regulated by the electric heating device, and the heating tube can be made of heat-conducting metal materials such as copper or aluminum. Further preferably, the copper tube is made of red copper material, and the thermal conductivity is 386.4W / (m·K), which has excellent thermal conductivity. The heat-conducting section of the electric heating tube is parallel to the fiber direction and does not contact the fiber. The temperature in the heating tube is 30℃~300℃. More preferably, it is 85℃~160℃.

[0163] The extruder is connected to a multi-nozzle spray head and is provided with a corresponding number of copper tubes, each of which corresponds to a nozzle of the spray head and is used to perform a corresponding cold treatment or heat treatment on the fibers passing through the copper tubes.

[0164] In one embodiment of the present invention, the post-processing process may optionally include a collection process, which is implemented via a collection unit. The collection unit includes a motor and a collection roller driven by the motor. The collection roller is controlled by the motor to rotate slowly. The existing control system can be used to control the speed of the motor to rotate and collect the fibers, thereby achieving continuous collection of the fibers.

[0165] The internal morphology of the microstructure fiber includes: circular pores or long strip pore structures parallel to the axial direction of the fiber.

[0166] In a specific embodiment of the present invention, the spinning solution is extruded through an extruder controlled by an extrusion pump, formed by a fiber forming solution, and passed through a low-temperature copper tube. Due to the low temperature, the water in the fiber condenses into ice crystals. At the same time, due to the microscopic phase separation of the system, the polymer is displaced by the ice crystals and compressed in the gaps between the ice crystals. After the cold treatment, the fiber is collected by a collecting drum. After being completely frozen, the ice crystals are removed by freeze drying to obtain microstructured fibers.

[0167] In a specific embodiment of the present invention, the extruder is connected to a multi-nozzle nozzle, a plurality of copper tubes are placed in parallel, all of the copper tubes are installed at the bottom of the freezing tank, multiple strands of fibers pass through the copper tubes at the same time, and the collecting roller collects the multiple strands of fibers at the same time, thereby achieving simultaneous cold treatment and collection of the multiple strands of fibers.

[0168] In a specific embodiment of the present invention, the spinning solution is extruded through an extruder controlled by an extrusion pump, formed by a fiber forming solution, and passed through a hot copper tube. Due to the response characteristics of the porogenic material inside the fiber to the high temperature environment, a pore structure is formed in the fiber. After the heat treatment, the fiber is collected by a collecting drum. The heat treatment time of the fiber can be controlled by adjusting the collection speed of the collecting drum.

[0169] In a specific embodiment of the present invention, the extruder is connected to a multi-nozzle nozzle, a plurality of electric heating copper tubes are placed side by side, all of the electric heating copper tubes are arranged parallel to the axial direction of the fiber, multiple strands of fibers pass through the electric heating copper tubes at the same time, and a collecting roller collects the multiple strands of fibers at the same time, thereby achieving simultaneous heat treatment and collection of the multiple strands of fibers.

[0170] The present invention provides a general and / or specific description of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % represents wt%, i.e., weight percentage. The reagents or instruments used without indicating the manufacturer are all conventional reagent products or conventional experimental instruments that can be purchased commercially.

[0171] Table 1 Experimental materials used

[0172]

[0173]

[0174] Example 1 Preparation of microstructured fibers

[0175] (1) Preparation of coating solution: 3 g of polyacrylonitrile was dissolved in 17 g of N,N-dimethylformamide solution at 85°C to prepare a 15% polyacrylonitrile solution.

[0176] (2) Preparation of core layer raw materials: 2 g of polyurethane was dissolved in 18 g of N,N-dimethylformamide solution at 85° C. to prepare a polyurethane solution, 0.1 g of 980DU120 was added to the polyurethane solution, the mass fraction of the polyurethane was 10%, and the mass fraction of 980DU120 in the polyurethane was 5%, and the mixture was stirred at a speed of 800 rpm / min for 30 min to mix them evenly to prepare the core layer raw materials.

[0177] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in the cladding extruder, the extruder nozzle is a single nozzle with one hole, and the shape is round. The nozzle component is a two-component coaxial structure. The solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously. The flow rate of the extrusion pump extrusion piston is 2m / min. The spinning stock solution forms nascent fibers in a forming bath filled with fiber forming liquid. The fiber forming liquid is water, and the fiber is heat-treated by passing through a guide wheel through a heating tube. The temperature for heat treatment of the nascent fibers is 160°C, and the stretching ratio is 1. Finally, the treated fibers are collected by a collecting drum to obtain microstructured fibers.

[0178] Example 2 Preparation of microstructured fibers

[0179] (1) Preparation of coating solution: 3 g of polyacrylonitrile was dissolved in 17 g of N,N-dimethylformamide solution at 85°C to prepare a 15% polyacrylonitrile solution.

[0180] (2) Preparation of core layer raw materials: 4 g of polyurethane was dissolved in 16 g of N,N-dimethylformamide solution at 85° C. to prepare a polyurethane solution, 0.2 g of 980DU120 was added to the polyurethane solution, the mass fraction of the polyurethane was 20%, and the mass fraction of 980DU120 in the polyurethane was 5%, and the mixture was stirred at a speed of 800 rpm / min for 30 min to mix them evenly to prepare the core layer raw materials.

[0181] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in the cladding extruder, the extruder nozzle is a single nozzle with one hole, and the shape is round. The nozzle component is a two-component coaxial structure. The solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously. The flow rate of the extrusion pump extrusion piston is 2m / min. The spinning stock solution forms nascent fibers in a forming bath filled with fiber forming liquid. The fiber forming liquid is water, and the fiber is heat-treated by passing through a guide wheel through a heating tube. The temperature for heat treatment of the nascent fibers is 160°C, and the stretching ratio is 1. Finally, the treated fibers are collected by a collecting drum to obtain microstructured fibers.

[0182] Example 3 Preparation of microstructured fibers

[0183] (1) Preparation of coating solution: 3 g of polyacrylonitrile was dissolved in 17 g of N,N-dimethylformamide solution at 85°C to prepare a 15% polyacrylonitrile solution.

[0184] (2) Preparation of core layer raw materials: 6 g of polyurethane was dissolved in 14 g of N,N-dimethylformamide solution at 85° C. to prepare a polyurethane solution, 0.3 g of 980DU120 was added to the polyurethane solution, the mass fraction of the polyurethane was 30%, and the mass fraction of 980DU120 in the polyurethane was 5%, and the mixture was stirred at a speed of 800 rpm / min for 30 min to mix them evenly to prepare the core layer raw materials.

[0185] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in the cladding extruder, the extruder nozzle is a single nozzle with one hole, and the shape is round. The nozzle component is a two-component coaxial structure. The solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously. The flow rate of the extrusion pump extrusion piston is 2m / min. The spinning stock solution forms nascent fibers in a forming bath filled with fiber forming liquid. The fiber forming liquid is water, and the fiber is heat-treated by passing through a guide wheel through a heating tube. The temperature for heat treatment of the nascent fibers is 160°C, and the stretching ratio is 1. Finally, the treated fibers are collected by a collecting drum to obtain microstructured fibers.

[0186] Example 4 Preparation of microstructured fibers

[0187] (1) Preparation of coating solution: 3 g of polyacrylonitrile was dissolved in 17 g of N,N-dimethylformamide solution at 85°C to prepare a 15% polyacrylonitrile solution.

[0188] (2) Preparation of core layer raw materials: 4 g of polyurethane was dissolved in 16 g of N,N-dimethylformamide solution at 85° C. to prepare a polyurethane solution, 0.4 g of 980DU120 was added to the polyurethane solution, the mass fraction of the polyurethane was 20%, and the mass fraction of 980DU120 in the polyurethane was 10%, and the mixture was stirred at a speed of 800 rpm / min for 30 min to mix them evenly to prepare the core layer raw materials.

[0189] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in the cladding extruder, the extruder nozzle is a single nozzle with one hole, and the shape is round. The nozzle component is a two-component coaxial structure. The solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously. The flow rate of the extrusion pump extrusion piston is 2m / min. The spinning stock solution forms nascent fibers in a forming bath filled with fiber forming liquid. The fiber forming liquid is water, and the fiber is heat-treated by passing through a guide wheel through a heating tube. The temperature for heat treatment of the nascent fibers is 160°C, and the stretching ratio is 1. Finally, the treated fibers are collected by a collecting drum to obtain microstructured fibers.

[0190] Example 5 Preparation of microstructured fibers

[0191] (1) Preparation of coating solution: 6 g of polyacrylonitrile was dissolved in 14 g of N,N-dimethylformamide solution at 85°C to prepare a 30% polyacrylonitrile solution.

[0192] (2) Preparation of core layer raw materials: 4 g of polyurethane was dissolved in 16 g of N,N-dimethylformamide solution at 85° C. to prepare a polyurethane solution, 0.2 g of 980DU120 was added to the polyurethane solution, the mass fraction of the polyurethane was 20%, and the mass fraction of 980DU120 in the polyurethane was 5%, and the mixture was stirred at a speed of 800 rpm / min for 30 min to mix them evenly to prepare the core layer raw materials.

[0193] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in the cladding extruder, the extruder nozzle is a single nozzle with one hole, and the shape is round. The nozzle component is a two-component coaxial structure. The solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously. The flow rate of the extrusion pump extrusion piston is 2m / min. The spinning stock solution forms nascent fibers in a forming bath filled with fiber forming liquid. The fiber forming liquid is water, and the fiber is heat-treated by passing through a guide wheel through a heating tube. The temperature for heat treatment of the nascent fibers is 160°C, and the stretching ratio is 1. Finally, the treated fibers are collected by a collecting drum to obtain microstructured fibers.

[0194] Example 6 Preparation of microstructured fibers

[0195] (1) Preparation of coating solution: 3 g of polyurethane was dissolved in 17 g of N,N-dimethylformamide solution at 85°C to prepare a 15% polyurethane solution.

[0196] (2) Preparation of core layer raw materials: 4 g of polyacrylonitrile was dissolved in 16 g of N,N-dimethylformamide solution at 85° C. to prepare a polyacrylonitrile solution, 0.2 g of 980DU120 was added to the polyacrylonitrile solution, the mass fraction of polyacrylonitrile was 20%, and the mass fraction of 980DU120 in polyacrylonitrile was 5%, and the mixture was stirred at a speed of 800 rpm / min for 30 min to mix them evenly to prepare the core layer raw materials.

[0197] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in the cladding extruder, the extruder nozzle is a single nozzle with one hole, and the shape is round. The nozzle component is a two-component coaxial structure. The solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously. The flow rate of the extrusion pump extrusion piston is 2m / min. The spinning stock solution forms nascent fibers in a forming bath filled with fiber forming liquid. The fiber forming liquid is water, and the fiber is heat-treated by passing through a guide wheel through a heating tube. The temperature for heat treatment of the nascent fibers is 160°C, and the stretching ratio is 1. Finally, the treated fibers are collected by a collecting drum to obtain microstructured fibers.

[0198] Example 7 Preparation of microstructured fibers

[0199] The difference between Example 7 and Example 2 is that the raw material polymer of the core layer is 4g polypropylene imine and 0.2g 980DU120, and the other conditions are the same as Example 2.

[0200] Example 8 Preparation of microstructured fibers

[0201] The difference between Example 8 and Example 2 is that the raw material polymer of the core layer is 4g polytetrafluoroethylene and 0.2g 980DU120, and the other conditions are the same as Example 2.

[0202] Example 9 Preparation of microstructured fibers

[0203] The difference between Example 9 and Example 2 is that the temperature for heat treating the as-spun fibers is 100° C., and the other conditions are the same as those in Example 2.

[0204] Example 10 Preparation of microstructured fibers

[0205] The difference between Example 10 and Example 2 is that the stretching ratio is 2, and the other conditions are the same as Example 2.

[0206] Example 11 Preparation of microstructured fibers

[0207] The difference between Example 11 and Example 2 is that the shape of the nozzle of the extruder is pentagonal, and the other conditions are the same as Example 2.

[0208] Example 12 Preparation of microstructured fibers

[0209] The difference between Example 12 and Example 2 is that the nozzle of the extruder is a two-component nozzle, and the nozzle has two holes, and the other conditions are the same as Example 2.

[0210] Example 13 Preparation of microstructured fibers

[0211] The difference between Example 13 and Example 2 is that the shape of the nozzle of the extruder is a triangle, the nozzle of the extruder is a four-component nozzle, and the other conditions are the same as Example 2.

[0212] Example 14 Preparation of microstructured fibers

[0213] The difference between Example 14 and Example 2 is that the shape of the nozzle of the extruder is pentagonal, the nozzle of the extruder is a four-component nozzle, and the other conditions are the same as Example 2.

[0214] Comparative Example 1 Preparation of microstructured fibers

[0215] The difference between Example 1 and Example 2 is that the raw material polymer of the core layer is 4g of polyurethane and 0.2g of sodium chloride, and the other conditions are the same as Example 2.

[0216] Comparative Example 2 Preparation of microstructured fibers

[0217] The difference between Example 2 and Example 2 is that the raw polymer of the core layer is 4g polyurethane and 0.2g sodium bicarbonate, and the other conditions are the same as Example 2.

[0218] Comparative Example 3 Preparation of microstructured fibers

[0219] The difference between Example 3 and Example 2 is that the raw polymer of the core layer is 4g polyurethane and 0.2g Expancel 043DU80, and the other conditions are the same as Example 2.

[0220] Comparative Example 4 Preparation of microstructured fibers

[0221] The difference between Example 4 and Example 2 is that the core layer raw polymer does not contain heat-expandable microspheres, and the other conditions are the same as Example 2.

[0222] Embodiment 21

[0223] (1) Preparation of coating solution: 6 g of polyurethane was dissolved in 14 g of N,N-dimethylformamide solution at 85° C. to prepare a 30% polyurethane solution.

[0224] (2) Preparation of core layer raw material: 4 g 920DU40 was dissolved in a small amount of toluene, 6 g polydimethylsiloxane was added, and the mixture was stirred for 5 h. The solvent was removed at a high temperature of 115°C, and then 0.6 g 184 silica gel was added as a curing agent. The mixture was stirred and the bubbles were removed by ultrasonication to obtain the core layer raw material.

[0225] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in the cladding extruder, the extruder nozzle is a single nozzle with one hole, and the shape is round. The nozzle component is a two-component coaxial structure. The solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously. The flow rate of the extrusion pump extrusion piston is 2m / min. The spinning stock solution forms nascent fibers in a forming bath filled with fiber forming liquid. The fiber forming liquid is water, and the fiber is heat-treated by passing through a guide wheel through a heating tube. The temperature for heat treatment of the nascent fibers is 160°C, and the stretching ratio is 1. Finally, the treated fibers are collected by a collecting drum to obtain microstructured fibers.

[0226] Embodiment 22

[0227] (1) Preparation of coating solution: 6 g of polyurethane was dissolved in 14 g of N,N-dimethylformamide solution at 85° C. to prepare a 30% polyurethane solution.

[0228] (2) Preparation of core layer raw material: 2 g 920DU40 was dissolved in a small amount of toluene, 8 g polydimethylsiloxane was added, and the mixture was stirred for 5 h. The solvent was removed at a high temperature of 115°C, and then 0.8 g 184 silica gel was added as a curing agent. The mixture was stirred and the bubbles were removed by ultrasonication to obtain the core layer raw material.

[0229] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in the cladding extruder, the extruder nozzle is a single nozzle with one hole, and the shape is round. The nozzle component is a two-component coaxial structure. The solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously. The flow rate of the extrusion pump extrusion piston is 2m / min. The spinning stock solution forms nascent fibers in a forming bath filled with fiber forming liquid. The fiber forming liquid is water, and the fiber is heat-treated by passing through a guide wheel through a heating tube. The temperature for heat treatment of the nascent fibers is 160°C, and the stretching ratio is 1. Finally, the treated fibers are collected by a collecting drum to obtain microstructured fibers.

[0230] Example 23 Preparation of microstructured fibers

[0231] The difference between Example 23 and Example 22 is that the temperature for heat treatment of the as-spun fiber is 100°C, and the other conditions are the same as Example 22.

[0232] Comparative Example 21 Preparation of microstructured fibers

[0233] The difference between Comparative Example 21 and Example 22 is that the core layer raw materials are as follows: 2 g of sodium chloride is dissolved in a small amount of toluene, 8 g of polydimethylsiloxane is added, stirred for 5 hours, the solvent is removed at a high temperature of 115°C, and then 0.8 g of 184 silica gel is added as a curing agent, stirred, and ultrasonically removed to obtain the core layer raw materials. The other conditions are the same as Example 22.

[0234] Comparative Example 22 Preparation of microstructured fibers

[0235] The difference between Comparative Example 22 and Example 22 is that the core layer raw materials are as follows: 2 g of sodium bicarbonate is dissolved in a small amount of toluene, 8 g of polydimethylsiloxane is added, stirred for 5 hours, the solvent is removed at a high temperature of 115°C, and then 0.8 g of 184 silica gel is added as a curing agent, stirred, and ultrasonically removed to obtain the core layer raw materials. The other conditions are the same as Example 22.

[0236] Comparative Example 23 Preparation of microstructured fibers

[0237] The difference between Comparative Example 23 and Example 22 is that the core layer raw materials are as follows: 2 g of Expancel043DU80 is dissolved in a small amount of toluene, 8 g of polydimethylsiloxane is added, stirred for 5 hours, the solvent is removed at a high temperature of 115°C, and then 0.8 g of 184 silica gel is added as a curing agent, stirred, and ultrasonically removed to obtain the core layer raw materials. The other conditions are the same as Example 22.

[0238] Comparative Example 24 Preparation of microstructured fibers

[0239] The difference between Comparative Example 24 and Example 22 is that the core layer raw materials are as follows: 8 g of polydimethylsiloxane is dissolved in a small amount of toluene, stirred for 5 hours, and the solvent is removed at a high temperature of 115°C. Then 0.8 g of 184 silica gel is added as a curing agent, stirred, and ultrasonically removed to obtain the core layer raw materials. The other conditions are the same as Example 22.

[0240] Embodiment 31

[0241] (1) Preparation of coating solution: 2.5 g of polyurethane was dissolved in 17.5 g of N,N-dimethylformamide solution at 85° C. to prepare a 12.5% ​​polyurethane solution.

[0242] (2) Preparation of core layer raw materials: 2 g of polyvinyl alcohol was dissolved in 38 g of water at 90° C. to prepare a 5% polyvinyl alcohol solution; 2 g of chitosan was dissolved in 38 g of 1% acetic acid solution, and stirred at 800 rpm / min for 30 min to mix them evenly to prepare a 5% chitosan solution; 9 ml of polyvinyl alcohol solution and 1 ml of chitosan solution were mixed evenly, and then centrifuged to remove bubbles to obtain a uniform solution, in which the mass ratio of polyvinyl alcohol to chitosan was 9:1, thus obtaining the core layer raw materials.

[0243] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in a cladding extruder, the extruder nozzle is a single nozzle with one hole, both of which are circular in shape, and the nozzle component is a two-component coaxial structure, the solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously, the flow rate of the extrusion pump extrusion piston is 2m / min, the spinning stock solution is formed into nascent fibers in a forming bath filled with fiber forming liquid, the fiber forming liquid is water, and the fiber is cold-treated by passing through a guide wire wheel through a freezing tank filled with a refrigerant, the refrigerant is liquid nitrogen, the temperature for cold-treating the nascent fibers is -100°C, the stretching ratio is 1, and finally the treated fibers are collected by a collecting drum, and the obtained fibers are freeze-dried for 24 hours to remove the solvent to obtain microstructured fibers.

[0244] Embodiment 32

[0245] The difference between Example 32 and Example 31 is that: after 8 ml of polyvinyl alcohol solution and 2 ml of chitosan solution are mixed evenly, centrifugation is performed to remove bubbles to obtain a uniform solution, wherein the mass ratio of polyvinyl alcohol to chitosan is 8:2, thus obtaining the core layer raw material, and the other conditions are the same as Example 31.

[0246] Embodiment 33

[0247] (1) Preparation of coating solution: 2.5 g of polyurethane was dissolved in 17.5 g of N,N-dimethylformamide solution at 85° C. to prepare a 12.5% ​​polyurethane solution.

[0248] (2) Preparation of core layer raw materials: 4 g of polyvinyl alcohol was dissolved in 36 g of water at 90° C. to prepare a 10% polyvinyl alcohol solution; 4 g of chitosan was dissolved in 36 g of 1% acetic acid solution, and stirred at 800 rpm / min for 30 min to mix them evenly to prepare a 10% chitosan solution; 9 ml of polyvinyl alcohol solution and 1 ml of chitosan solution were mixed evenly, and then centrifuged to remove bubbles to obtain a uniform solution, in which the mass ratio of polyvinyl alcohol to chitosan was 9:1, thus obtaining the core layer raw materials.

[0249] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in a cladding extruder, the extruder nozzle is a single nozzle with one hole, both of which are circular in shape, and the nozzle component is a two-component coaxial structure, the solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously, the flow rate of the extrusion pump extrusion piston is 2m / min, the spinning stock solution is formed into nascent fibers in a forming bath filled with fiber forming liquid, the fiber forming liquid is water, and the fiber is cold-treated by passing through a guide wire wheel through a freezing tank filled with a refrigerant, the refrigerant is liquid nitrogen, the temperature for cold-treating the nascent fibers is -100°C, the stretching ratio is 1, and finally the treated fibers are collected by a collecting drum, and the obtained fibers are freeze-dried for 24 hours to remove the solvent to obtain microstructured fibers.

[0250] Embodiment 34

[0251] (1) Preparation of coating solution: 2.5 g of polyurethane was dissolved in 17.5 g of N,N-dimethylformamide solution at 85° C. to prepare a 12.5% ​​polyurethane solution.

[0252] (2) Preparation of core layer raw material: Dissolve 2 g of polyvinyl alcohol in 38 g of water at 90° C. to prepare a 5% polyvinyl alcohol solution to obtain the core layer raw material.

[0253] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in a cladding extruder, the extruder nozzle is a single nozzle with one hole, both of which are circular in shape, and the nozzle component is a two-component coaxial structure, the solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously, the flow rate of the extrusion pump extrusion piston is 2m / min, the spinning stock solution is formed into nascent fibers in a forming bath filled with fiber forming liquid, the fiber forming liquid is water, and the fiber is cold-treated by passing through a guide wire wheel through a freezing tank filled with a refrigerant, the refrigerant is liquid nitrogen, the temperature for cold-treating the nascent fibers is -100°C, the stretching ratio is 1, and finally the treated fibers are collected by a collecting drum, and the obtained fibers are freeze-dried for 24 hours to remove the solvent to obtain microstructured fibers.

[0254] Embodiment 35

[0255] (1) Preparation of coating solution: 2.5 g of polyurethane was dissolved in 17.5 g of N,N-dimethylformamide solution at 85° C. to prepare a 12.5% ​​polyurethane solution.

[0256] (2) Preparation of core layer raw material: 2 g of chitosan was dissolved in 38 g of 1% acetic acid solution, and stirred at 800 rpm / min for 30 min to mix them evenly to prepare a 5% chitosan solution to obtain the core layer raw material.

[0257] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in a cladding extruder, the extruder nozzle is a single nozzle with one hole, both of which are circular in shape, and the nozzle component is a two-component coaxial structure, the solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously, the flow rate of the extrusion pump extrusion piston is 2m / min, the spinning stock solution is formed into nascent fibers in a forming bath filled with fiber forming liquid, the fiber forming liquid is water, and the fiber is cold-treated by passing through a guide wire wheel through a freezing tank filled with a refrigerant, the refrigerant is liquid nitrogen, the temperature for cold-treating the nascent fibers is -100°C, the stretching ratio is 1, and finally the treated fibers are collected by a collecting drum, and the obtained fibers are freeze-dried for 24 hours to remove the solvent to obtain microstructured fibers.

[0258] Embodiment 36

[0259] (1) Preparation of coating solution: 2.5 g of polyurethane was dissolved in 17.5 g of N,N-dimethylformamide solution at 85° C. to prepare a 12.5% ​​polyurethane solution.

[0260] (2) Preparation of core layer raw material: 2 g of polyacrylonitrile was dissolved in 38 g of N,N-dimethylformamide solution at 85° C. to prepare a 5% polyacrylonitrile solution to obtain the core layer raw material.

[0261] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in a cladding extruder, the extruder nozzle is a single nozzle with one hole, both of which are circular in shape, and the nozzle component is a two-component coaxial structure, the solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously, the flow rate of the extrusion pump extrusion piston is 2m / min, the spinning stock solution is formed into nascent fibers in a forming bath filled with fiber forming liquid, the fiber forming liquid is water, and the fiber is cold-treated by passing through a guide wire wheel through a freezing tank filled with a refrigerant, the refrigerant is liquid nitrogen, the temperature for cold-treating the nascent fibers is -100°C, the stretching ratio is 1, and finally the treated fibers are collected by a collecting drum, and the obtained fibers are freeze-dried for 24 hours to remove the solvent to obtain microstructured fibers.

[0262] Embodiment 37

[0263] (1) Preparation of coating solution: 2.5 g of polylactic acid was dissolved in 17.5 g of N,N-dimethylformamide solution at 85° C. to prepare a 12.5% ​​polylactic acid solution.

[0264] (2) Preparation of core layer raw materials: 2 g of polyvinyl alcohol was dissolved in 38 g of water at 90° C. to prepare a 5% polyvinyl alcohol solution; 2 g of chitosan was dissolved in 38 g of 1% acetic acid solution, and stirred at 800 rpm / min for 30 min to mix them evenly to prepare a 5% chitosan solution; 9 ml of polyvinyl alcohol solution and 1 ml of chitosan solution were mixed evenly, and then centrifuged to remove bubbles to obtain a uniform solution, in which the mass ratio of polyvinyl alcohol to chitosan was 9:1, thus obtaining the core layer raw materials.

[0265] (3) placing the core layer raw material in a core layer extruder, placing the cladding solution in a cladding extruder, the extruder nozzle is a single nozzle with one hole, both of which are circular in shape, and the nozzle component is a two-component coaxial structure, the solution is extruded through the extruder piston, and then coaxial spinning is performed simultaneously, the flow rate of the extrusion pump extrusion piston is 2m / min, the spinning stock solution is formed into nascent fibers in a forming bath filled with fiber forming liquid, the fiber forming liquid is water, and the fiber is cold-treated by passing through a guide wire wheel through a freezing tank filled with a refrigerant, the refrigerant is liquid nitrogen, the temperature for cold-treating the nascent fibers is -100°C, the stretching ratio is 1, and finally the treated fibers are collected by a collecting drum, and the obtained fibers are freeze-dried for 24 hours to remove the solvent to obtain microstructured fibers.

[0266] Embodiment 38

[0267] The only difference between Example 38 and Example 31 is that the temperature for cold treatment of the spun fiber is -196°C, and the other conditions are the same.

[0268] Comparative Example 31

[0269] The difference between Comparative Example 31 and Example 31 is that the spinning solution is first placed at -100°C for pre-cooling, and then spinning is carried out.

[0270] The important implementation parameters in the above Examples 1-9 and Comparative Examples 1-4 are shown in Table 2

[0271] Table 2

[0272]

[0273] The important implementation parameters in the above Examples 21-23 and Comparative Examples 21-24 are shown in Table 3

[0274] Table 3

[0275]

[0276] The important implementation parameters in the above Examples 31-37 are shown in Table 4

[0277]

[0278]

[0279] Experimental Example 1

[0280] Thermal conductivity is measured using the iXIATECH TC3000E thermal conductivity tester (transient hot wire method). The ideal model of the transient hot wire method is a radial one-dimensional non-steady-state heat conduction problem in an infinite medium, specifically a heat conduction process caused by an infinitely long hot wire in an infinite medium in an initial thermal equilibrium state and a transient heating pulse. A typical set of measurement processes, from preparing for the test to obtaining the final data, generally only takes 2 to 3 minutes; on the premise that the sample and sensor have been connected and the instrument has been connected, the automatic multiple acquisition function in the software can also be used. The data only needs to be exported after the test, and no conversion is required.

[0281] The mechanical properties are tested according to GB 13022-1991 standard. The instrument is an electronic universal testing machine (non-metallic direction), model CMT4202 / ZWICK / Z020.

[0282] The pore size, porosity and specific surface area can be determined in accordance with ISO 15901 "Evaluation of pore size distribution and porosity of materials by pressure and gas adsorption". The test principle is to fill the pores with mercury by pressure. Mercury does not wet general solids. To make mercury enter the pores, external pressure must be applied. The greater the external pressure, the smaller the radius of the pore that mercury can enter. By measuring the amount of mercury entering the pores under different external pressures, the pore volume of the corresponding pore size can be known, and the porosity can be calculated.

[0283] The pore size is calculated as follows:

[0284] Using the fact that the external pressure is inversely proportional to the net width of the mercury inlet hole, for cylindrical holes, the Washburn equation gives the relationship between pressure and pore diameter, as shown in Equation 1:

[0285]

[0286] Applying equation 1, the pore size can be calculated.

[0287] The specific surface area is calculated as follows:

[0288] Assuming cylindrical pores, the surface distribution can be derived from the pore volume distribution. According to the research of Rootare and Prenzlow, assuming that the sample must not contain ink bottle-shaped pores and does not deform under external pressure, the specific surface area of ​​the mercury-entering pores can be calculated from the pressure / volume curve without applying a pore model, as shown in Equation 2:

[0289]

[0290] From the function V=V(p), the integral can be calculated graphically or by means of numerical methods.

[0291] The pore size calculated at maximum pressure is 3 nm. Since the surface area of ​​pores smaller than 3 nm is not measured (estimated to be small), and the surface area of ​​the ink bottle-shaped pores is calculated using a cylindrical pore model based on the bottleneck diameter (estimated to be large), it is incomparable with the results obtained by gas adsorption.

[0292] Table 5 Experimental data results of various embodiments and comparative examples

[0293]

[0294]

[0295] It can be seen from Table 5 that the microstructured fibers prepared in Examples 1-10, Examples 21-23, and Examples 31-38 have excellent thermal insulation properties on the basis of having and satisfying mechanical properties.

[0296] Thermal conductivity is a physical quantity that indicates the thermal conductivity of a material:

[0297] Q = KA △ T / d,

[0298] K-thermal conductivity, Q-heat flow, △T-temperature difference between upper and lower surfaces, d-distance between upper and lower surfaces, A-contact area

[0299] When the heat flux Q, the temperature difference between the upper and lower surfaces △T, the distance d between the upper and lower surfaces, and the contact area A are constant, the thermal conductivity is only related to the temperature difference. When the porosity is larger, the heat transfer between the upper and lower surfaces is slower, the temperature difference is larger, and the thermal conductivity will decrease.

[0300] It can be seen from Table 5 that the thermal conductivity of Examples 1-9 is significantly better than that of Comparative Examples 1-4, and the thermal conductivity is negatively correlated with the porosity, that is, the greater the porosity, the lower the thermal conductivity value and the better the thermal insulation performance.

[0301] The heat-expandable microspheres selected in the present invention are better than the sodium chloride, sodium bicarbonate and Expancel 043DU80 selected in the comparative examples. It can be seen from the comparative examples that when the heat-expandable microspheres are not used, their porosity and thermal insulation performance are poor. In addition, the thermal insulation performance of Examples 1-5 is significantly better than that of Examples 6-8, indicating that when the core layer polymer is polyurethane and the cladding polymer is polyacrylonitrile, the thermal insulation performance is better than that of other polymers. The thermal insulation performance when the heat treatment temperature is 160°C is better than the thermal insulation performance when the heat treatment temperature is 100°C. In the heat treatment process, when the core layer polymer is polyurethane, the softening point temperature of polyurethane matches the expansion temperature of the microspheres, and the mechanical properties are relatively good. At the same time, when the skin layer is polyacrylonitrile, the softening temperature of polyacrylonitrile is higher, and the skin layer has a certain shape-keeping ability when the microspheres expand.

[0302] The thermal insulation performance of Examples 21-23 is significantly better than that of Comparative Examples 23-24, indicating that the thermal insulation performance of the microstructure fiber prepared by the heat-expandable microspheres selected in the present invention is significantly better than that of the microstructure fiber prepared by Expancel 043DU80 selected in Comparative Example 23. When the heat-expandable microspheres are not added, the thermal insulation performance is very poor. The thermal insulation performance when the heat treatment temperature is 160°C is better than the thermal insulation performance when the heat treatment temperature is 100°C, indicating that in the heat treatment process, when the polymer is a thermosetting polymer, such as polydimethylsiloxane, spinning can be performed without adding a solvent. Compared with the case where the heat treatment temperature is 100°C, when the heat treatment temperature is 160°C, the heat-expandable microspheres are easy to form pores in the fiber, the porosity is increased, and the thermal conductivity is reduced.

[0303] When the applicant implemented Comparative Examples 21-22, it was found that the solution could not form a pore structure at all, indicating that when sodium chloride and sodium bicarbonate were used to replace the heat-expandable microspheres of the present invention, the preparation process of the present invention could not produce a pore structure.

[0304] In Examples 31-37, the thermal insulation performance of Examples 31-33 is significantly better than that of Examples 34-35, indicating that in the cold treatment process, when the core layer polymer is a mixture of polyvinyl alcohol and chitosan, its thermal insulation performance is significantly better than when the core layer polymer is selected from polyvinyl alcohol or chitosan alone. This indicates that in the cold treatment process, when the core layer polymer is a mixture of polyvinyl alcohol and chitosan, the thermal insulation performance is better than other polymers. The two polymers play a synergistic role. Polyvinyl alcohol is a water-soluble material and is skin-friendly, which can reduce the viscosity of chitosan.

[0305] When the applicant implemented Comparative Example 31, it was found that the scheme of Comparative Example 31 could not be implemented. The spinning solution had turned into a solid state at minus 100°C and could not be squeezed out during wet spinning, making it impossible to form a microstructure.

[0306] The above is only the preferred implementation of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present application without departing from the content of the technical solution of the present application still belongs to the protection scope of the technical solution of the present application.

Claims

1. A microstructure fiber, comprising a core layer and a cladding layer, wherein the cladding layer covers the core layer, the core layer has a microstructure, the core layer comprises a first polymer and heat-expandable microspheres, and the cladding layer comprises a second thermoplastic polymer; The porosity of the microstructure of the core layer is 70-90%; The preparation process of the microstructured fiber comprises the following steps: i configure the spinning solution, the spinning solution comprises a core material and a cladding solution; ii. Spinning process: wet spinning the spinning solution to obtain nascent fibers; iii. Post-treatment process: post-treating the primary fibers to obtain microstructured fibers; The post-treatment process is a heat treatment process; In the heat treatment process, the temperature of heat treatment on the as-spun fiber is 160°C, and the heat treatment is electric heating treatment; When the first polymer is a first thermoplastic polymer, the first thermoplastic polymer is polyurethane; the second thermoplastic polymer is polyacrylonitrile, and the heat-expandable microspheres are 980DU120; or, When the first polymer is a first thermosetting polymer, the first thermosetting polymer is polydimethylsiloxane, the second thermoplastic polymer is polyurethane, and the heat-expandable microspheres are 920DU40.

2. The microstructured fiber according to claim 1, wherein The diameter ratio of the core layer and the cladding layer in the cross section of the microstructure fiber is 1:1.1-1:

5.

3. The microstructured fiber according to claim 1, wherein The pore size of the microstructure of the core layer is 0.1-200 μm, and the specific surface area of ​​the microstructure fiber is 1-400 m 2 / g.

4. The microstructured fiber according to claim 3, wherein: The pore size is 10-40 μm, and the specific surface area is 50-100 m 2 / g.

5. A microstructure fiber, comprising a core layer and a cladding layer, wherein the cladding layer covers the core layer, and both the core layer and the cladding layer have a microstructure, the core layer comprises a third polymer, the third polymer is composed of chitosan and polyvinyl alcohol, and the mass ratio of polyvinyl alcohol to chitosan is 9:1 or 8:2, and the cladding layer is polyurethane or polylactic acid; The core layer has a microstructure with a porosity of 70-90%; The preparation process of the microstructured fiber comprises the following steps: i configure the spinning solution, the spinning solution comprises a core material and a cladding solution; ii. Spinning process: wet spinning the spinning solution to obtain nascent fibers; iii. Post-treatment process: post-treating the primary fibers to obtain microstructured fibers; The post-treatment process is a cold treatment process; The cold treatment process includes cooling treatment and freeze drying treatment, and the temperature of the cooling treatment on the primary fiber is -196°C to -100°C.

6. The microstructured fiber according to claim 5, wherein: The diameter ratio of the core layer and the cladding layer in the cross section of the microstructure fiber is 1:1.1-1:

5.

7. The microstructured fiber according to claim 5, wherein The core layer has a microstructure with a pore size of 0.1-200 μm, the cladding has a microstructure with a pore size of 0.1-100 μm, the cladding has a microstructure with a porosity of 5-99%, and the microstructure fiber has a specific surface area of ​​1-400 m 2 / g.

8. The microstructured fiber according to claim 7, wherein: The pore size of the microstructure of the core layer is 0.2-100 μm, the pore size of the microstructure of the cladding layer is 0.2-100 μm, the porosity of the microstructure of the core layer is 70-90%, and the specific surface area is 50-100 m 2 / g.

9. The microstructured fiber according to any one of claims 1 to 8, wherein in step i, the solvent used to form the spinning solution is selected from one or more of chloroform, dichloromethane, N,N-dimethylformamide, tetrahydrofuran solvent, chloroform, acetone, tetrachloroethylene, methyl acetate, ethylenediamine, ethyl acetate, and toluene.

10. The microstructured fiber according to claim 5, wherein In the cooling process, a refrigerant is selected to cool the spun fibers.

11. The microstructured fiber according to claim 10, wherein: The refrigerant is selected from one or more of liquid nitrogen, dry ice, ethanol and ethylene glycol.

12. The microstructured fiber according to claim 1 or 5, wherein in step i, the solvent of the coating solution is selected from one or more of N,N-dimethylacetamide, N,N-dimethylformamide, methanol, formic acid, chloroform, acetone, tetrachloroethylene, methyl acetate, ethyl acetate, and toluene.

13. The microstructured fiber according to any one of claims 1 or 5, wherein in step ii, the spinning process comprises an extrusion process and a molding process; In the extrusion process, a core layer raw material is placed in a core layer extruder, and a cladding solution is placed in the cladding extruder, and then wet spinning is performed.

14. The microstructured fiber according to claim 13, wherein: The core layer raw material extrusion flow rate is 0.01-100 m / min.

15. The microstructured fiber according to claim 14, wherein: The core layer raw material extrusion flow rate is 1-5 m / min.

16. The microstructured fiber according to claim 13, wherein: The cladding solution extrusion flow rate is 0.01-100 m / min.

17. The microstructured fiber according to claim 16, wherein: The cladding solution extrusion flow rate is 1-5 m / min.

18. The microstructure fiber according to any one of claims 14 to 17, wherein in the extrusion process, the spinning solutions are extruded in parallel. 19 . The microstructure fiber according to claim 18 , wherein in the molding process, the spinning solution is molded using a fiber molding solution.

20. The microstructured fiber according to claim 19, wherein The fiber forming liquid is selected from one or more of ethanol, methanol, water, ethylene glycol, isobutyl alcohol, isopentanol, benzyl alcohol, sodium sulfate and sodium hydroxide solution.

21. The microstructured fiber according to claim 20, wherein The fiber forming liquid is water.

Citation Information

Patent Citations

  • tio2 hollow fully mesoporous nanofibers

    CN105019054B

  • High-imitation cotton textile fiber and preparation method thereof

    CN107475819A

  • Three-dimensional support material containing hierarchical porous structures and preparation and application

    CN106390208A

  • Conductive polymer composite fiber with skin-core structure and preparation method thereof

    CN106968023A

  • Foamable fiber

    JP2011256479A